1986
DOI: 10.1111/j.1600-0447.1986.tb02700.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between EEG and clinical characteristics in major depressive disorder

Abstract: Twenty-five patients with major depressive disorder (MDD) according to RDC were examined with computerized EEG before antidepressive treatment was initiated. Relationships between EEG parameters and clinical characteristics were studied. Age and pharmacological treatment were taken into account. Primary MDD was associated with an increase of delta amplitude. Retarded MDD was associated with an increase of delta and theta amplitudes and EEG variability. Recurrent unipolar MDD was related to a decrease of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
2
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 8 publications
(2 reference statements)
5
38
2
2
Order By: Relevance
“…And the global coherence of the MDD group is significantly higher than that of the healthy group in the theta band (4-8 Hz). In alpha (8-13 Hz) and beta bands (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), there is no diacritic difference in both groups.…”
Section: Global Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…And the global coherence of the MDD group is significantly higher than that of the healthy group in the theta band (4-8 Hz). In alpha (8-13 Hz) and beta bands (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), there is no diacritic difference in both groups.…”
Section: Global Coherencementioning
confidence: 99%
“…Using this approach, a large number of findings were presented in the study of the depression. Some results based on EEG oscillations demonstrated that patients with MDD had more frontal theta, alpha, and beta oscillations [18][19][20]. Using EEG oscillations, Lee et al [21] suggested that the brain affected by a major depressive disorder showed a slower decay of the long-range temporal (auto)correlations (LRTC).…”
Section: Complexitymentioning
confidence: 99%
“…If posterior alpha-theta training were done with an alcoholic who also had problems with ADHD and who did not have an excess of beta activity, might this exacerbate the ADHD? Alcoholics also frequently suffer with comorbid depression, which many studies (Alper, 1995;Brenner et al, 1986;Itil, 1983;John et al, 1988;Knott & Lapierre, 1987;Monakhov & Perris, 58 JOURNAL OF NEUROTHERAPY 1980;Nystrom, Matousek, & Hallstrom, 1986;Pollock & Schneider, 1990;Nieber & Schlegel, 1992) have found may be associated with an alpha or theta excess. Is it possible that training to enhance alpha or theta might increase depression in such a person?…”
mentioning
confidence: 99%
“…In depression, EEG-delta/theta augmentation (Knott and Lapierre, 1987;Llinas et al, 1999;Vo1f and Passynkova, 2002;Nystrom et al, 1986), reduction (Brenner et al, 1986;Knott et al, 2000), and no change from controls (Visser et al, 1985;Pollock and Schneider, 1990) have heen reported. Differences between studies may have resulted from age differences, given that higher age may vary with increased risk for cognitive impairment or dementia.…”
mentioning
confidence: 99%